1999
DOI: 10.1016/s0378-1097(99)00160-3
|View full text |Cite
|
Sign up to set email alerts
|

The expression of the flagellum of Legionella pneumophila is modulated by different environmental factors

Abstract: Legionella pneumophila, the aetiologic agent of legionnaires' disease, contains a single, monopolar flagellum which is composed of one major subunit, the FlaA protein. Expression studies using a reporter gene fusion of the flaA promoter with the luxAB gene revealed that the flaA expression is not only temperature regulated but is also influenced by the growth phase, the viscosity and the osmolarity of the medium, and by amino acids. z

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
25
0
2

Year Published

2000
2000
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 16 publications
(31 reference statements)
4
25
0
2
Order By: Relevance
“…pillar-and mushroom-like structures) formed at 25 u C remained more stably attached than filamentous, mycelial-mat-like biofilms formed at 37 and 42 u C. Also, Mampel et al (2006) reported that biofilm formation at 37 u C was 30 % lower than at 23 and 30 u C. Furthermore, we have shown that adhesion is highest for late stationary phase cells. This is expected, as L. pneumophila shows increased expression of the flagellum and of type IV pili, both of which have been described in other bacteria to be involved in adhesion (O'Toole & Kolter, 1998;Pratt & Kolter, 1998;Watnick & Kolter, 1999), in stationary phase during low-temperature growth (Heuner et al, 1999;Soderberg et al, 2004). Because stationary phase mimics the transmissive phase in which bacteria are released from amoebae (Molofsky & Swanson, 2004), our observations suggest that bacteria that exit host cells in natural lowtemperature environments are in an optimal physiological state to adhere to biofilms.…”
Section: Discussionsupporting
confidence: 74%
“…pillar-and mushroom-like structures) formed at 25 u C remained more stably attached than filamentous, mycelial-mat-like biofilms formed at 37 and 42 u C. Also, Mampel et al (2006) reported that biofilm formation at 37 u C was 30 % lower than at 23 and 30 u C. Furthermore, we have shown that adhesion is highest for late stationary phase cells. This is expected, as L. pneumophila shows increased expression of the flagellum and of type IV pili, both of which have been described in other bacteria to be involved in adhesion (O'Toole & Kolter, 1998;Pratt & Kolter, 1998;Watnick & Kolter, 1999), in stationary phase during low-temperature growth (Heuner et al, 1999;Soderberg et al, 2004). Because stationary phase mimics the transmissive phase in which bacteria are released from amoebae (Molofsky & Swanson, 2004), our observations suggest that bacteria that exit host cells in natural lowtemperature environments are in an optimal physiological state to adhere to biofilms.…”
Section: Discussionsupporting
confidence: 74%
“…Error bars show SD. *Significant difference between the calibrator and the time post-infection have a contrary effect (Heuner et al 1999). Additionally, the regulatory genes of the P. salmonis flagellar cascade share similar expression profiles to those described for L. pneumophila, where rpoN (σ54) and fliA (σ28) are induced, triggering a high expression of the final genes in the cascade, such as flaA and flaB (Prouty et al 2001, McCarter 2006.…”
Section: Discussionmentioning
confidence: 68%
“…3A). As a control for the growth phases, we analyzed the expression of flagellin (FlaA) by L. pneumophila harvested at the indicated growth phase because it is known that the expression of flagellin is highly induced in PE phase of L. pneumophila (2,47). As expected, the bacteria did not express flagellin in the replicative phase (EE ϩ LE), whereas FlaA was detected in PE and S phases (Fig.…”
Section: Construction and Growth Characterization Of L Pneumophila Mmentioning
confidence: 99%
“…When nutrients become limiting, L. pneumophila differentiates into the mature intracellular form. This phase corresponds to the transmissive phase in which L. pneumophila becomes flagellated, expresses its virulence factors, and seems to be metabolically dormant (1)(2)(3)(4). This biphasic life cycle is also observed during growth in liquid medium, and therefore, in vitro experiments are considered as valid models to analyze the specific features encountered during both phases (3).…”
mentioning
confidence: 99%